Cultural Identity in Children's Books: Multilingualism and Cultural Pride in The Name Jar - Muhammad Arifandi Yacub; Firja Adica; Adrian David Rafael Siburian; Rafi Isham Fadhlillah; Muhammad Yusuf (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Children's literature contributes immensely towards constructing the cultural identities of immigrants and minority language learners, but research focusing on analyzing particular multilingual picture books from a multimodal perspective is scarce. The current research focuses on the analysis of The Name Jar (Choi, 2001) as a multilingual picture book in order to understand the ways’ cultural identity representations are created and negotiated in a Korean-American environment. A qualitative case study methodology was used where multimodal content analysis (Krippendorff, 2019; Kress & van Leeuwen, 2006) and thematic analysis (Braun & Clarke, 2006) techniques were applied to the verbal text, illustrations, paratext, and Korean-script sections of the book. Four themes were derived: cultural identity through naming; text as a mirror and window; visualizing multilingualism; and pedagogical possibilities of the text. The findings of the current research demonstrate that The Name Jar creates a complex counter-narrative of assimilation by promoting hybrid identity while the Korean script is more than just a decoration but also a multimodal semiotic resource. Overall, multilingual picture books like The Name Jar have great potential as pedagogical materials for intercultural education and promoting the heritage language identity.